THE EFFECT OF NURSING ENGLISH LEARNING BASED ON NEEDS ANALYSIS ON NURSING STUDENTS' ENGLISH PROFICIENCY - Risman Wanci; Sujariati Sujariati; Ambo Anto (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
English is a medium for international communication and an essential language in extensive medical literature and research investigations, as seen by the numerous health books authored in English. The objective of this research is to investigate how English learning based on needs analysis affects the English language skills of nursing students. This research employed a pre-experimental approach to assess the impact of needs analysis-oriented English language instruction on nursing students' proficiency in English. This method was used as it enabled researchers to monitor alterations in students' English language proficiency post-intervention without necessitating a control group. The results of this study show that the mean scores were different; in the pretest, it was 31.45, while in the posttest, it was 69.65. This means that the students' English achievement in the posttest mean score was higher than the pretest. The posttest mean score is higher than the pretest mean score; the increase was 38.20. Besides that, the probability value was smaller than the level of significance 0.05. In conclusion, there is a significant difference between the pretest and posttest scores. The authors hope that the English nursing book used in this study will be useful to many people